2018
DOI: 10.3389/fpls.2018.01601
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wheat to a Multiple Species Microbial Inoculant Compared to Fertilizer Application

Abstract: Microbial inoculants, including those formed from multiple species, may have dual functions as biostimulants and/or biocontrol agents, and claimed agricultural benefits are instrumental for regulatory categorisation. Biostimulants include commercial products containing substances or microorganisms that stimulate plant growth. Biostimulant microbes can be involved in a range of processes that affect N and P transformations in soil and thus influence nutrient availability, and N and P fertilizers can influence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…Use of biological agents, such as nitrogenfixing bacteria, plant growth promoting rhizobacteria, mycorrhizal fungi and organisms for the biological control of pests and diseases, is an alternative to increase yields in several crops in agroecological systems (O'Callaghan, 2016;Assainar et al, 2018;Togni et al, 2019). In addition to the use of commercial products, onfarm multiplication of inoculants has also been evaluated (Englander;Douds;Mallory, 2016;Hart et al, 2018) and already being used by farmers, along with simple techniques of multiplication and asepsis, to reduce the cost with inoculants.…”
Section: Agroecological Intensification Of Farming Systemsmentioning
confidence: 99%
“…Use of biological agents, such as nitrogenfixing bacteria, plant growth promoting rhizobacteria, mycorrhizal fungi and organisms for the biological control of pests and diseases, is an alternative to increase yields in several crops in agroecological systems (O'Callaghan, 2016;Assainar et al, 2018;Togni et al, 2019). In addition to the use of commercial products, onfarm multiplication of inoculants has also been evaluated (Englander;Douds;Mallory, 2016;Hart et al, 2018) and already being used by farmers, along with simple techniques of multiplication and asepsis, to reduce the cost with inoculants.…”
Section: Agroecological Intensification Of Farming Systemsmentioning
confidence: 99%
“…The success of microbial inoculants as biostimulants is varied and may not be predictable ( Qiu et al, 2019 ). For example, in previous studies of the use of a multispecies microbial inoculant applied to wheat, there was a positive response in grain yield ( Assainar et al, 2018 ). The microbial inoculant influenced the relative abundance of rhizosphere bacteria, especially Actinobacteria.…”
Section: Introductionmentioning
confidence: 98%
“…Plant growth responses to some biostimulants could influence the soil microbial community and provide greater plant access to less soluble nutrients ( Calvo et al, 2014 ). Biostimulants include multispecies microbial inoculants and may be used alone (e.g., Assainar et al, 2018 ) or in combination with fertilizers (e.g., Assainar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stamford et al showed that biofertilizers influenced positively on total N, available P, available K, exchangeable Ca 2+ and Mg 2+ in soil and also increased the grape yield as compared to the control when applied at a depth of 0-20 cm [12]. Soil microbial communities perform key functions of maintaining soil productivity [16]. Some researchers have shown that soil microbial community diversity was obviously affected due to the use of biofertilizers [17].…”
Section: Introductionmentioning
confidence: 99%